The phase stability of nanosecond Gunn oscillators - Kozhevnikov, Vasily Y.; Kozyrev, Andrey V.; Konev, Vladimir Y.; Klimov, Aleksey I. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: Detailed theoretical and experimental studies have been carried out in order to investigate the problem of a phase stability in electrodynamically uncoupled Gunn oscillators.Methods: The influence of modulating pulse instabilities has been investigated by means of computer simulation in the framework of a nonlinear one-dimensional theoretical model of the GaAs Gunn diode semiconductor active region. Experimental observations were also conducted including microwave measurements and antenna far-field estimation. They confirm the main theoretical results and extend the key work conclusions.Results: It was shown that the initial phase of the microwave oscillation out of the Gunn oscillator is independent of internal noises of the semiconductor structure and can be fixed only by the modulating voltage pulse.Conclusion: Gunn-diodes based microwave oscillators were stabilized using the leading edge of the voltage pulse from the modulating power supply. These results open up serious prospects for designing antenna phased arrays based on Gunn oscillators without mutual feedback (electrodynamically independent).
Keywords: microwave circuits; space-charge-limited devices; Gunn effect devices